Epigenetic targeting to enhance acute myeloid leukemia-directed immunotherapy - Rausch, Johanna; Ullrich, Evelyn; Kühn, Michael W.M. (Frontiers in Immunology, 2023)
AML is a malignant disease of hematopoietic progenitor cells with unsatisfactory outcome, especially in patients that are ineligible for intensive treatment. Immunotherapy, comprising checkpoint inhibition, T-cell engaging antibody constructs, and cellular therapies, has dramatically improved the outcome of patients with solid tumors and lymphatic neoplasms. In AML, these approaches have been far less successful. Discussed reasons are the relatively low mutational burden of AML blasts and the difficulty in defining AML-specific antigens not expressed on hematopoietic progenitor cells. On the other hand, epigenetic dysregulation is an essential driver of leukemogenesis, and non-selective hypomethylating agents (HMAs) are the current backbone of non-intensive treatment. The first clinical trials that evaluated whether HMAs may improve immune checkpoint inhibitors' efficacy showed modest efficacy except for the anti-CD47 antibody that was substantially more efficient against AML when combined with azacitidine. Combining bispecific antibodies or cellular treatments with HMAs is subject to ongoing clinical investigation, and efficacy data are awaited shortly. More selective second-generation inhibitors targeting specific chromatin regulators have demonstrated promising preclinical activity against AML and are currently evaluated in clinical trials. These drugs that commonly cause leukemia cell differentiation potentially sensitize AML to immune-based treatments by co-regulating immune checkpoints, providing a pro-inflammatory environment, and inducing (neo)-antigen expression. Combining selective targeted epigenetic drugs with (cellular) immunotherapy is, therefore, a promising approach to avoid unintended effects and augment efficacy. Future studies will provide detailed information on how these compounds influence specific immune functions that may enable translation into clinical assessment.